Application of lichenometry and residual strength test for age estimation of Holocene moraines in the Suntar-Khayata Mountains - A. A. Galanin; V. M. Lytkin; B. A. Shishkov (Лëд и снег)
Residual strength and diameters of lichen Rhizocarpon sp. were measured on different elements of the Late Holocene glacial-cryogenic morphosculpture of frontal parts of glaciers № 29 and 31 in the Suntar-Khayat Range. All in all, 180 lichenometric sites (about 1000 individual measurements of Rhizocarpon sp.) and 150 sites for testing the residual strength of rebound value were organized, on which 380 estimations of this parameter (5674 individual measurements) were performed. For lichenometric index of age (minimal time of exposure) we used statistics RH5 that was a mean value from five maximal individuals on a local site; for index of rebound value Q that was a mean value from 80-100 unit measurements on the same site was taken. Using of data obtained at different times by aerospace surveys made it possible to derive the relationship between the RH5 statistics and time t of the morphosculptures exposure: RH5 = 0.0535t + 0.29. On the basis of regression coefficients of RH5 and Q indexes the equation RH5 = 69209e-0,136Q had been deduced as well as the equation connecting residual strength (rebound value) Q and time t of surface exposure: t = (69209e-0,136Qvalue– 0,29)/0,0535. Basing on the equations above, age of the moraine belts of the above glaciers was estimated. The most developed moraine belt, now placed apart from the present-day glacier edges at a distance of 600–700 m, was found to be formed for the whole Little Ice Age. Glaciers reached their maximum volumes during its first phase, i.e. during cold period of 13-15th centuries. Area of glacierization exceeded its current size by 35–40%. Glaciers remained at their almost steady state until middle of 19th century and then began to retreat slowly. By middle of 20th century, glaciers shortened by 5–7%. The most intensive shrinking of these glaciers started in the second half of 20th century.